Spatial Distribution of Marine Debris on Northern Coastal Waters of Minahasa - Moningka, Ivana Trixie Louisa; Sangari, Joudy R. R.; Wantasen, Adnan S.; Lumingas, Lawrence J. L.; Moningkey, Ruddy D.; Pelle, Wilmy E. (Jurnal Ilmiah Platax, 2021)
Marine debris is one of the biggest pollution problems in the world. There are various potentials of marine and beach tourism to attract tourists, but in turn, cause a waste disposal accumulation and coupled with the built-in garbage that comes from the sea. The research was conducted at Tasik Ria Beach, Tombariri, and Marine Field Station of the Faculty of Fisheries and Marine Sciences, Sam Ratulangi University in Likupang. The aims of this study were (1) to identify the types of marine debris, and (2) to determine and compare the spatial distribution pattern of marine debris in the two designed locations. The sampling technique adapted from the shoreline survey methodology designed by NOAA was used in the study. Data were then statistically processed and analyzed using data mining software (MS Excel and Orange). This study found that the category of plastic and rubber waste is the most common category with the total amount on Tasik Ria Beach 54.39% and 97.55% in the Marine Field Station of Faculty of Fisheries and Marine Sciences in Likupang respectively. The correlation coefficient between the composition of the amount and mass of marine debris is 0.89 which indicates a close relationship between the amount and mass composition. There are many factors that cause the distribution of various types of marine debris, one of which is the activities of the people around the coastal area.Keywords: Marine debris; Category; Type; CompositionAbstrakSampah laut merupakan salah satu masalah polusi yang besar di dunia. Beragam potensi wisata bahari dan pantai menjadi daya tarik wisatawan namun aktivitas wisata dapat mengakibatkan adanya buangan sampah oleh masyarakat dan wisatawan, ditambah lagi dengan sampah bawaan yang berasal dari laut. Penelitian ini dilakukan di Pantai Tasik Ria, Tombariri dan Laboratorium Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi untuk mengidentifikasi jenis sampah laut di perairan pantai Minahasa bagian utara dan mengetahui persebaran dan perbandingan distribusi sampah laut dua lokasi penelitian. Berdasarkan hasil pengambilan sampel dengan mengadaptasi metode Shoreline Survey Methodology berdasarkan NOAA yang kemudian diolah dan dianalisis secara statistik dengan menggunakan beberapa perangkat lunak (MS Excel dan Orange) diperoleh kategori sampah plastik dan karet sebagai kategori yang paling banyak ditemukan dengan komposisi jumlahnya di Pantai Tasik Ria sebesar 54,39% dan 97,55% di Laboratorium Fakultas Perikanan dan Ilmu Kelautan. Nilai koefisien korelasi antara komposisi jumlah dan massa sampah laut sebesar 0.89 yang menyatakan hubungan yang erat antara komposisi jumlah dan massa. Banyaknya faktor yang menyebabkan terdistribusinya beragam jenis sampah laut, salah satunya adalah aktivitas masyarakat di sekitar wilayah pesisir.Kata kunci: Sampah Laut; Kategori; Jenis; Komposisi